MiR-126-3p and MiR-223-3p as Biomarkers for Prediction of Thrombotic Risk in Patients with Acute Myocardial Infarction and Primary Angioplasty - Hromadka, Milan; Motovska, Zuzana; Hlinomaz, Ota; Kala, Petr; Tousek, Frantisek; Jarkovsky, Jiri; Beranova, Marketa; Jansky, Pavel; Svoboda, Michal; Krepelkova, Iveta; Rokyta, Richard; Widimsky, Petr; et al. (Journal of personalized medicine, 2021)
Aim. This study was designed to evaluate the relationship between microRNAs (miRNAs), miR-126-3p and miR-223-3p, as new biomarkers of platelet activation, and predicting recurrent thrombotic events after acute myocardial infarction (AMI). Methods and Results. The analysis included 598 patients randomized in the PRAGUE-18 study (ticagrelor vs. prasugrel in AMI). The measurements of miRNAs were performed by using a novel miRNA immunoassay method. The association of miRNAs with the occurrence of the ischemic endpoint (EP) (cardiovascular death, nonfatal MI, or stroke) and bleeding were analyzed. The miR-223-3p level was significantly related to an increased risk of occurrence of the ischemic EP within 30 days (odds ratio (OR) = 15.74, 95% confidence interval (CI): 2.07-119.93, p = 0.008) and one year (OR = 3.18, 95% CI: 1.40-7.19, p = 0.006), respectively. The miR-126-3p to miR-223-3p ratio was related to a decreased risk of occurrence of EP within 30 days (OR = 0.14, 95% CI: 0.03-0.61, p = 0.009) and one year (OR = 0.37, 95% CI: 0.17-0.82, p = 0.014), respectively. MiRNAs were identified as independent predictors of EP even after adjustment for confounding clinical predictors. Adding miR-223-3p and miR-126-3p to miR-223-3p ratios as predictors into the model calculating the ischemic risk significantly increased the predictive accuracy for combined ischemic EP within one year more than using only clinical ischemic risk parameters. No associations between miRNAs and bleeding complications were identified. Conclusion. The miR-223-3p and the miR-126-3p are promising independent predictors of thrombotic events and can be used for ischemic risk stratification after AMI.
Keywords: miR-223-3p; antithrombotic therapy individualization; miR-126-3P; acute myocardial infarction; risk stratification; microRNA